2001
DOI: 10.1007/s004290000139
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of somatostatin-28 (1-12) immunoreactivity in the diencephalon and the brainstem of the dog

Abstract: The term somatostatin refers to a family of peptides, mainly somatostatin-14, somatostatin-28 and somatostatin-28 (1-12), which are the cleavage products of a single 116 amino acid-long preprosomatostain molecule. The production of antibodies to these peptides allows their localization in a number of neuronal populations throughout the entire neuroaxis in many mammals. The dog has been pointed out as an extremely useful animal model for studying age-related cognitive dysfunction and other neuronal changes asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…In contrast, we found that SOM 28 AA1-12 was present at high abundance in the superior colliculus. This is also consistent with previous findings based on autoradiography measurements in mouse [49], dog [50] and sheep [51] colliculus. This shows that different members of the Somatostatin family are expressed preferentially in different parts of the visual system.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, we found that SOM 28 AA1-12 was present at high abundance in the superior colliculus. This is also consistent with previous findings based on autoradiography measurements in mouse [49], dog [50] and sheep [51] colliculus. This shows that different members of the Somatostatin family are expressed preferentially in different parts of the visual system.…”
Section: Discussionsupporting
confidence: 93%
“…Also, sections were incubated omitting the primary antibody used in this study and no labelling was detected in any case. In addition, as previously reported (Coveñas et al, ; de León et al, ; Martín et al, ; Pego‐Reigosa et al, ), the preabsorption of the primary antibody with an excess of synthetic somatostatin‐28, somatostatin‐14, neuropeptide Y, angiotensin II, substance P, cholecystokinin, and methionine‐enkephalin was also carried out. Staining was not blocked in any of the cases.…”
Section: Methodsmentioning
confidence: 97%
“…The polyclonal primary antibody was raised in rabbits against immunogens prepared by coupling the synthetic peptide [somatostatin‐28 (1‐12)] to human serum albumin with glutaraldehyde, as previously reported (Coveñas et al, ; de León et al, ; Martín et al, ; Pego‐Reigosa et al, ). Rabbits were initially immunized with immunogens emulsified with Freund's complete adjuvant and at 2‐week intervals they were given booster doses of Freund's incomplete adjuvant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a dearth of neuroanatomical data on the organization of the neurotransmitter systems in this species and on the response of these systems to aging (Kojima et al, 1983;Tafti et al, 1997). In this line of research, we have studied the anatomical organization of several neurotransmitter and neuropeptide systems in the brain of the dog Tomé et al, 1997;Pego-Reigosa et al, 2000;Pego-Reigosa et al, 2001;Pesini et al, 2001). The aim of the present work is to examine the distribution of ACTH in the brainstem of the dog and to compare it with the anatomical organization of the monoaminergic systems in this species and with previous reports on the distribution of ACTH in other mammals.…”
Section: Introductionmentioning
confidence: 97%